Discovery Learning in E-Book with Natural Science Lesson at Elementary School - Ni Komang Asih Kurnia Dewi (Universitas Pendidikan Ganesha, 2022)
This research was motivated by problems in the media and learning models that were less innovative and varied during the online learning process, so it impacted students' lack of understanding, especially on the content of science lessons. This study aims to develop an e-book based on discovery learning for elementary science lessons. The subjects in this study were content experts, instructional design experts, learning media experts, and fifth-grade elementary school students. This research is development research by applying the ADDIE model. Data collection in this study was done by using a questionnaire method with quantitative descriptive analysis techniques. Based on the results of data analysis, the following results were obtained: 1) content experts 95.00%, 2) instructional design experts 93.75%, 3) learning media experts 87.50%, 4) individual trial results 83.33%, 5) small group trial results 90.50%. Thus the conclusions in this study indicate that this e-book based on discovery learning is in very good qualification and is suitable for use in science learning for fifth-grade elementary school.